Genetic Mapping of Race‐Specific Stem Rust Resistance in the Synthetic Hexaploid W7984 × Opata M85 Mapping Population. Issue 6 (1st November 2015) - Dunckel, Sandra M.; Olson, Eric L.; Rouse, Matthew N.; Bowden, Robert L.; Poland, Jesse A.
ABSTRACT: Stem rust (caused by Puccinia graminis f. sp. tritici ) has historically caused severe yield losses of wheat ( Triticum aestivum L.) worldwide and has been one of the most feared diseases of wheat and barley ( Hordeum vulgare L.). Stem rust has been controlled successfully through the use of resistant varieties. However, stem rust lineage Ug99 and its derivatives are virulent to many widely deployed stem rust resistance genes including Sr31 . Doubled haploid lines from the Synthetic W7984 × Opata M85 wheat reference population were screened for seedling resistance to P. graminis f. sp. tritici races TRTTF and QTHJC. The phenotypic data were adjusted to a 1 to 5 scale and genes for resistance to races TRTTF and QTHJC were localized using composite interval mapping (CIM). Major effect quantitative trait loci (QTLs) for resistance to stem rust races TRTTF and QTHJC were identified on chromosome arms 1AS, 2BS, 6AS, and 6AL. The gene for resistance to both races on 2BS could potentially be a new stem rust resistance gene. The QTLs for resistance on 1AS and 6AL might be other new genes or alleles while the QTL on 6AS is likely an Sr8 allele. Future work will determine if the resistance loci on 1AS, 2BS, and 6AL are novel. As shown here, the well studied Synthetic × Opata reference population is a valuable source of potentially novel resistance genes for stem rust that can be leveraged in resistance breeding programs.